Synthesis of Hybrid Thiohemicucurbiturils via Acid-Catalyzed Conversion - Wang, Ai-Jiao; Han, Jian-Jie; Ren, Ming-He; Wang, Li; Peng, Xiang-Bo; Zhang, Qian-Jun; Ge, Qing-Mei; Cong, Hang; Liu, Mao (Current Organic Chemistry, 2026)
Thiocrown ethers, thiocalixarenes, and thiocyclodextrins, as important host macrocycles, have been synthesized as crown ether, calixarene, and cyclodextrin derivatives, respectively. They have shown special properties compared with their prototypes. Hemicucurbiturils, as a subset of cucurbiturils, are yet to have their thio-derivatives. In this article, methods for the synthesis of hybrid thiohemicucurbiturils were proposed, and several hybrid thiohemicucurbiturils were formed. The mono ethylene thiourea-substituted hemicucurbituril was formed by simply mixing ethylene thiourea and ethylene urea with formaldehyde in an HCl aqueous solution. The synthesis of more ethylene thioureas-substituted hemicucurbituril by acid-catalyzed conversion of an ethylene thiourea-substituted hemicucurbituril has been presented, which differs from the traditional method for synthesizing hemicucurbituril derivatives. These methods provide alternatives for the synthesis of novel hybrid hemicucurbiturils with more complex structures.
Keywords: Thiohemicucurbiturils